Aging-related gains and losses associated with word production in connected speech. Issue 6 (1st November 2016) - Dennis, Paul A.; Hess, Thomas M.
ABSTRACT: Older adults have been observed to use more nonnormative, or atypical, words than younger adults in connected speech. We examined whether aging-related losses in word-finding abilities or gains in language expertise underlie these age differences. Sixty younger and 60 older adults described two neutral photographs. These descriptions were processed into word types, and textual analysis was used to identify interrupted speech (e.g., pauses), reflecting word-finding difficulty. Word types were assessed for normativeness, with nonnormative word types defined as those used by six (5%) or fewer participants to describe a particular picture. Accuracy and precision ratings were provided by another sample of 48 high-vocabulary younger and older adults. Older adults produced more interrupted and, as predicted, nonnormative words than younger adults. Older adults were more likely than younger adults to use nonnormative language via interrupted speech, suggesting a compensatory process. However, older adults' nonnormative words were more precise and trended for having higher accuracy, reflecting expertise. In tasks offering response flexibility, like connected speech, older adults may be able to offset instances of aging-related deficits by maximizing their expertise in other instances.